Homestay tourism in Baramulla: economic, socio-cultural, and environmental insights / Ajaz Ahmad Dar, Danish Iqbal Raina and Sajad Ahmad Bhat - Ahmad Dar, Ajaz; Raina, Danish Iqbal; Ahmad Bhat, Sajad (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2024)
Homestay tourism, characterized by travelers residing in the homes of local hosts, offers a distinctive and immersive experience that fosters cultural exchange. This study investigates the impacts of homestay tourism on the local community, with a particular focus on the Baramulla District in the Kashmir Valley. The research draws on the perspectives of homestay operators to examine the economic, sociocultural, and environmental impacts associated with this form of tourism. The primary aim of this study is to assess the economic, sociocultural, and environmental impacts of homestay tourism on the local community, while also exploring potential variations in how these impacts are perceived by different segments of the local population. This research employs a quantitative design, utilizing a self-constructed questionnaire administered to 60 homestay operators, with the sample size determined through power analysis. The data are analyzed using statistical techniques, including the Student’s t-test and Regression Analysis, to draw inferences from the responses. The findings indicate that homestay operators generally hold favorable views regarding the economic benefits of homestay tourism, particularly in relation to the stimulation of local businesses, the creation of employment opportunities, and the improvement of income levels among residents. There were no significant differences observed in the operators’ perceptions of the economic and sociocultural impacts of homestay tourism. Additionally, the environmental impacts of homestay tourism were perceived as minimal, with little concern regarding ecological degradation among the operators.